The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/3234013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Surgery under General Anesthesia and the Development of Dementia: A Systematic Review and Meta-Analysis

Abstract: Objective. To investigate the association between exposure to general anesthesia and the development of Alzheimer’s disease (AD) and dementia by reviewing and integrating the evidence from epidemiological studies published to date. Methods. We searched MEDLINE, EMBASE, and Google Scholar to identify all relevant articles up to April 2018 reporting the risk of AD/dementia following exposure to general anesthesia and finally updated in February 2020. We included patients older than 60 or 65 years who had not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 72 publications
1
18
0
1
Order By: Relevance
“…On the other hand, it has been reported that a spike of tau hyperphosphorylation happens after brain injury 76 and general anesthesia 77 , due likely to acutely diminished phosphatase activities 78 , 79 . Whether this transient tau hyperphosphorylation is related to the positive association between dementia and traumatic brain injury 13 or exposure to general anesthesia 80 remains an open question. Animal studies may provide a clue as to whether R-(−)-apomorphine can be used to neutralize hyperphosphorylated tau following brain injury or general anesthesia exposure, thus reducing the likelihood of AD and ADRD after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that a spike of tau hyperphosphorylation happens after brain injury 76 and general anesthesia 77 , due likely to acutely diminished phosphatase activities 78 , 79 . Whether this transient tau hyperphosphorylation is related to the positive association between dementia and traumatic brain injury 13 or exposure to general anesthesia 80 remains an open question. Animal studies may provide a clue as to whether R-(−)-apomorphine can be used to neutralize hyperphosphorylated tau following brain injury or general anesthesia exposure, thus reducing the likelihood of AD and ADRD after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide population-based cohort studies found significant associations between GA and dementia [17,27]. However, previous meta-analyses yielded conflicting results [28][29][30]. One meta-analysis reported a significant positive association between GA and AD [30], but others found only weak or no links [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous meta-analyses yielded conflicting results [28][29][30]. One meta-analysis reported a significant positive association between GA and AD [30], but others found only weak or no links [28,29]. Thus, any association between anesthesia and dementia remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest a possible link between anesthesia and AD in humans [ 31 , 32 ], while more recent ones do not [ 33 , 34 ]. Also, as stated by Lee et al it is nearly impossible to discriminate the influence of general anesthesia from the effect of surgery itself on the development of AD [ 35 ].…”
Section: Introductionmentioning
confidence: 99%